1999
DOI: 10.1063/1.124059
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-vacancy-related dielectric anomalies in La:SrTiO3

Abstract: Effects of 2 nm size added heterogeneity on non-exponential dielectric response, and the dynamic heterogeneity view of molecular liquids J. Chem. Phys. 137, 104502 (2012) Radiowave dielectric investigation of water confined in channels of carbon nanotubes J. Chem. Phys. 137, 094908 (2012) Effect of Pr substitution on structural and dielectric properties of SrTiO3 J. Appl. Phys. 112, 044106 (2012) Response delay caused by dielectric relaxation of polymer insulators for organic transistors and resolution meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 20 publications
1
32
2
Order By: Relevance
“…However, recently, some of the present authors confirmed that this dielectric loss peak is actually related to oxygen vacancies, due to its disappearance after lengthy annealing in an oxidizing atmosphere. 17 For STO thin films obtained from different deposition processes, the preparation conditions including partial pressures of oxygen atmosphere, the cooling rate, etc., may vary greatly for different samples; this has influence on the concentration of the oxygen vacancies. It is reasonable to assume that the difference in the concentration of oxygen vacancies leads to the appearance of mode I in some samples and disappearance in other samples.…”
Section: Dielectric Loss Modes Of Srtio 3 Thin Films Deposited On Difmentioning
confidence: 99%
“…However, recently, some of the present authors confirmed that this dielectric loss peak is actually related to oxygen vacancies, due to its disappearance after lengthy annealing in an oxidizing atmosphere. 17 For STO thin films obtained from different deposition processes, the preparation conditions including partial pressures of oxygen atmosphere, the cooling rate, etc., may vary greatly for different samples; this has influence on the concentration of the oxygen vacancies. It is reasonable to assume that the difference in the concentration of oxygen vacancies leads to the appearance of mode I in some samples and disappearance in other samples.…”
Section: Dielectric Loss Modes Of Srtio 3 Thin Films Deposited On Difmentioning
confidence: 99%
“…However, precise determination of the absolute values of the bulk conductivity is difficult because in the temperature range 400-800 K large frequency dependent dielectric anomalies occur [10][11][12][13]. Such anomalies are qualitatively similar to those observed in perovskite-type crystals [3][4][5][14][15][16][17]. In general these anomalies can be due to complex dispersion phenomena in the bulk of the crystals [3-5, 15, 17] as well as to artefacts such as space charge relaxations in the crystal-electrode interface or disturbed layers close to the crystal surface [14,16,18].…”
Section: Introductionmentioning
confidence: 90%
“…It is well known that point defects strongly modify the conductive and dielectric properties of oxide materials and that the slow kinetics of such defects can determine the relaxation behavior of different physical properties and structural transformations [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric properties of nonstoichiometric ST ceramics are evaluated as a function of temperature and frequency in the radio frequency range. 3 . In this case, strontium vacancies are introduced as charge compensation.…”
Section: Introductionmentioning
confidence: 99%